Research on Weibo Health Communication Effectiveness and Strategies for Risk Groups - Zhao, Xin; Yin, Huiying; Dong, Yuewen; Ji, Jing (The Journal of Medicine, Humanity and Media, 2025)
Health communication, as an integral part of health and wellness culture construction, plays a pivotal role in enhancing public health literacy and fostering societal consensus. The evaluation of its effectiveness is crucial for refining communication strategies and promoting the development of health culture. This study constructs an indicator system to evaluate the effectiveness of health communication targeting risk populations. Based on 586,000 data instances from 13 typical health communication cases on the Weibo platform, this study conducts an empirical investigation into the communication effectiveness for health risk populations. By examining the dimensions of health information perception, health demand satisfaction, and health message adoption, the study analyzes the effectiveness of these cases, uncovers behavior patterns among risk groups, and accordingly proposes recommendations for refining communication strategies. Ultimately, this contributes to formulating targeted and precise health communication strategies.